A Novel Dual HDAC6 and Tubulin Inhibitor, MPT0B451, Displays Anti-tumor Ability in Human Cancer Cells in Vitro and in Vivo - Wu, Yi-Wen; Hsu, Kai-Cheng; Lee, Hsueh-Yun; Huang, Tsui-Chin; Lin, Tony E.; Chen, Yi-Ling; Sung, Ting-Yi; Liou, Jing-Ping; Hwang-Verslues, Wendy W.; Pan, Shiow-Lin; HuangFu, Wei-Chun (Frontiers in Pharmacology, 2018)
The combination cancer therapy is a new strategy to circumvent drug resistance for the treatment of high metastasis and advanced malignancies. Herein, we developed a synthesized compound MPT0B451 that display inhibitory effect against histone deacetylase (HDAC) 6 and tubulin assembly. Our data demonstrated that MPT0B451 significantly inhibited cancer cell growths in HL-60 and PC-3 cells due to inhibition of HDAC activity. MPT0B451 also markedly increased caspase-mediated apoptosis in these cells. The cell cycle analysis showed mitotic arrest induced by MPT0B451 with enhanced expression of G2/M transition proteins. Moreover, molecular docking analysis supported MPT0B451 as a dual HDAC6 and tubulin inhibitor. Finally, MPT0B451 led to tumor growth inhibition (TGI) in HL-60 and PC-3 xenograft models. These findings indicated that MPT0B451 has dual inhibition effects for HDAC6 and tubulin, and also contributed to G2/M arrest followed by apoptotic induction. Together, our results suggested that MPT0B451 may serve as a potent anti-cancer treatment regimen in human prostate cancer and acute myeloid leukemia.